A Strategies for Preventing and Handling Child Violence Through Assertive Training Methods in Banyuwangi Regency - Yuli Fitria; Wahyu Adri Wirawati; Machria Rahman (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Child violent abuses were fatally unrevealed because of the children’s inability to report and they do not even realize that they become victims of the abuse. Assertive training is expected to be an alternative method that can be used to improve children’s communicating their thoughts and feelings. Therefore, it needs to be proven through research. The objective of this study is to test the effectiveness of assertive training as a method to prevent and handle violence against children and improving children’s social skills in the form of assertive abilities. The study is a mixed method approaches and used purposive sampling technique. The sample were 100 students at two public junior high schools in Banyuwangi. For data analysis, the study used Paired Sample T- Test. The results of research showed assertive training had positive impact and was proven significantly increasing the assertive abilities. From the provision of assertive training, the children’s improved social skills were courage in expressing feelings, increased self-esteem, optimism and resilience. It can be concluded that the assertive training is able to increase assertive abilities, thus it can be an alternative method to prevent and handle violence against children. Keywords: Assertive, training, violence, children